Micro/nano-manufacturing of bioinspired blood-repellent surfaces for extreme application in surgical electrodes - Kaikai Li; Yingxi Xie; Pengyu Shen; Min Yu; Jiao Gao; Junming Bi; Long Wang; Longsheng Lu (International Journal of Extreme Manufacturing)
Surgical electrodes are frequently associated with disadvantages such as high surface adhesion and severe thermal damage to adjacent normal tissues, which threaten operation quality and patient safety. In this study, by mimicking the micromorphology and bio-anti-adhesion of shark skin, we proposed a strategy that utilized nanoscale aluminium oxide (Al _2 O _3 ) films deposited on bioinspired shark skin (BSS) microstructures to design a composite surface (Al _2 O _3 @BSS) and integrated it into both flat sides of the surgical electrodes. Micro/nano-manufacturing of the Al _2 O _3 @BSS surface was sequentially accomplished using nanosecond laser texturing, atomic layer deposition, and low-temperature annealing, endowing it with excellent blood-repellent properties. Visualisation experiments revealed that the tensile stress gradient of the blood coagulum with increasing thickness under a thermal field prompted it to separate from the Al _2 O _3 @BSS surface, resulting in anti-adhesion. Furthermore, it was observed for the first time that Al _2 O _3 films could transiently excite discharge along a dielectric surface (DADS) to ablate tissues while suppressing Joule heat, thereby minimising thermal damage. A combination of ex vivo tissue and living mouse experiments demonstrated that the Al _2 O _3 @BSS electrodes exhibited optimal comprehensive performance in terms of anti-adhesion, damage minimisation, and drag reduction. In addition, the Al _2 O _3 @BSS electrodes possessed remarkable antibacterial efficacy against E. coli and S. aureus . The proposed strategy can meet the extreme application requirements of surgical electrodes to improve operation quality and offer valuable insights for future studies.